Number 26 (December 1992) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1992)
(December 1992) - Fishes of Okatoma Creek, a Free-flowing Stream in South-Central Mississippi. By S.T. Ross et al., 9 pp. Reidentification of William Bartram's Savannah River Ambloplites, with Early Evidence for a Tennessee-Savannah Faunal Exchange. By R.C. Cashner, et al., 4 pp.
Keywords: fishes; okatoma creek; savannah river; ambloplites; fanual